1991
DOI: 10.1073/pnas.88.21.9377
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of insulin aggregation in aqueous solutions upon agitation in the presence of hydrophobic surfaces.

Abstract: The stability of protein-based pharmaceuticals (e.g., insulin) is important for their production, storage, and delivery. To gain an understanding ofinsulin's aggregation mechanism in aqueous solutions, the effects of agitation rate, interfacial interactions, and insulin concentration on the overall aggregation rate were examined. Ultraviolet absorption spectroscopy, high-performance liquid chromatography, and quasielastic light scattering analyses were used to monitor the aggregation reaction and identify inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
405
0
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 486 publications
(422 citation statements)
references
References 31 publications
15
405
0
2
Order By: Relevance
“…The agitation made by the shaking or stirring of a solution is known to cause protein aggregation (27,28). Consistent with this, Kad et al (8) observed the formation of many large amorphous aggregates during a lag phase.…”
Section: Ultrasonication-induced Fibrilsupporting
confidence: 63%
“…The agitation made by the shaking or stirring of a solution is known to cause protein aggregation (27,28). Consistent with this, Kad et al (8) observed the formation of many large amorphous aggregates during a lag phase.…”
Section: Ultrasonication-induced Fibrilsupporting
confidence: 63%
“…In agreement with this idea, an inverse correlation has recently been proposed between the stability of the prion aggregate and their incubation times in vivo (Legname et al, 2006), a finding which is closely analogous to the corresponding results obtained for yeast prions (Toyama et al, 2007;Tanaka et al, 2004). It is frequently found that for in vitro growth assays of many amyloid fibril systems agitation significantly enhances the overall conversion rate of proteins into fibrillar form (Sluzky et al, 1991;DePace et al, 1998;Serio et al, 2000;Ohhashi et al, 2005;Atarashi et al, 2007;Kim et al, 2007), an indication that modulations of fibril breakage are essential factors determining the rate of amyloid formation in general. In living systems, the rate constants for the multiplication of prions are clearly influenced not only by the intrinsic strength of the aggregates but also by other cellular components; molecular chaperones in yeast, for instance, have been identified as vital actors in this context (DebBurman et al, 1997;Shorter and Lindquist, 2004).…”
Section: Physical and Structural Determinants Of Prion Strainssupporting
confidence: 63%
“…However, the presence of an air-water or a water-oil interface, formed during emulsification, may lead to aggregation and fibril formation of an aqueous solution of insulin (Sluzky et al, 1991). The protein must maintain intact its three-dimensional structure and chemical integrity during the encapsulation process to allow the delivery of the native protein upon administration (Cleland, 1997).…”
Section: Bioactivitymentioning
confidence: 99%